Web-Based Software Development as Information Media and Digital Bulletin to Improve the Quality of Educational Services - Widya Febrianti; Ririn; Fany Ayu Hasanah; Adriel Malvin; Berliana Denita; Widiatry (International Journal of Technology and Education Research, 2026)
e rapid and transparent delivery of information is a key pillar in improving the quality of education in schools. However, there are currently significant limitations in the process of distributing information from schools to parents or guardians. Furthermore, the lack of an official forum for collecting suggestions and criticism from parents/guardians hinders schools in continuously evaluating and improving educational services. This research aims to develop a digital platform that integrates a school information center with a digital bulletin feature as a forum for aspirations. This software development was carried out usingThe prototype method encompasses the stages of requirements analysis, system modeling, system design, and functionality testing. This method allows for ongoing interaction between developers and stakeholders to ensure the digital bulletin features meet field needs. This research is expected to improve the quality of school information distribution and strengthen synergy between the institution and parents